Temporal drift in calibration of Ir-192 brachytherapy sources: A multi-center study on dosimetric discrepancies and metrological consistency - Javier Vijande; Jacob G. Johansen; Marisol De Brabandere; Taran Paulsen Hellebust; Antonio Herreros; Christian Kirisits; Ruud van Leeuwen; Panagiotis Papagiannis; Mark J. Rivard; Frank-André Siebert; Frank Verhaegen; Jan Wiersma; et al. (Physics and Imaging in Radiation Oncology, 2025)
Background and purpose: High-dose-rate (HDR) brachytherapy relies on accurate and metrologically traceable source strength determination. Recent anecdotal reports and preliminary studies have suggested a possible temporal drift in the reference air kerma rate (RAKR) measured by clinical users compared to manufacturer certificates for 192Ir sources. This study investigates the existence and magnitude of such drift across a large, multicenter European dataset and explores potential underlying causes. Materials and methods: A total of over 1700 RAKR measurements for HDR and PDR brachytherapy sources, collected over two decades from 29 centers in 10 European countries, were analyzed. The ratio of hospital-measured RAKR to manufacturer-certified RAKR was assessed using linear regression and t-tests to evaluate drift. Data were corrected for center-dependent systematics and segmented around key dates corresponding to changes in primary standards. Supplementary analyses included leave-one-out testing and time-segmented trend assessment. Results: A statistically significant drift (+0.15 %/year) was detected for all 192Ir source types after 2018, correlating temporally with updates in the German Physikalisch-Technische Bundesanstalt (PTB) primary standards laboratory. Removing PTB corrections from manufacturer values nearly eliminated the observed drift. No such trend was observed for 60Co sources. Conclusion: The findings reveal a drift in hospital-to-manufacturer Ir-192 RAKR ratios that is temporally correlated with changes in metrology standards, not uniformly implemented across calibration chains. The true cause is however still unknown. The study aimed to investigate that greater transparency and harmonization among all stakeholders are essential to ensure dosimetric accuracy in HDR brachytherapy.